PENGARUH PERTUMBUHAN PERUSAHAAN, TOTAL ASSET TURNOVER (TATO), EARNING PER SHARE (EPS) DAN PPH BADAN TERHADAP HARGA SAHAM (STUDI KASUS PEUSAHAAN SEKTOR INDUSTRI PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Imdan Soalihin; Jeni Susyanti; Muhammad Agus Salim (UNIVERSITAS ISLAM MALANG, 2019)
Abstract This research was conducted with the aim of partially analyzing the growth of the Company, Total Asset Turnover (TATO) and Earning Per Share (EPS) and corporate income tax on the company's stock prices in the mining industry sector. The population used in this study were all companies registered with Manufacturing Companies during the period 2016 to 2018. The selection of samples used the purposive sampling method. Based on the criteria obtained 19 companies. The method used is multiple linear regression analysis with hypothesis testing using the t test and f test. Partial company growth has a positive and significant influence on stock prices. Total asset turnover (TATO) partially has a positive and significant effect on stock prices. Earning Per Share (EPS) partially has a positive and significant effect on stock prices, partially corporate income tax have a negative and not significant effect on stock prices and company growth, total asset turnover, earnings per share and tax rates simultan eously have a positive and significant effect on prices stockKeywords: Company growth, Total asset turnover (TATO) and Earning Per Share (EPS), Corporate income tax ratessimultaneously have a positive and significant effect on prices stock rates and stock prices.